EFFECTIVENESS ASSESSMENT STUDY OF THE USE OF ICT TOOLS IN E-LEARNING SYSTEM - Mohammad, Malli (European Scientific Journal, ESJ, 2014)
The learning system is currently in the transition phase from classic learning system which rely on hard copies of text materials and whiteboard to the modern learning system which is often denoted as E-learning system. This new learning methodology strongly rely on technology in delivering the information to the students. This paper aims to evaluate the efficiency of the use of ICT tools in today’s learning system. This is done by firstly identifying the technical tools which are of great benefits in improving the content delivered to the students and then by emphasizing on their efficient usage. Through survey study, we validate that ICT tools should be integrated in the learning system in a more efficient way than just using slides that summarize the content presented in the book. Besides, we have studied the importance of practicing other modern technical tools as mainly simulation software which is able to support the text material by dynamic models that can help the student to in-depth his/her understanding and better clarify the textual presentation of the course materials provided to the students in the slides and textbooks.